2007
DOI: 10.1080/03610910701569044
|View full text |Cite
|
Sign up to set email alerts
|

Robust Multivariate Outlier Labeling

Abstract: A criterion for robust estimation of location and covariance matrix is considered, and its application in outlier labeling is discussed. This method, unlike the methods based on MVE and MCD, is applicable to large and high-dimension data sets. The method proposed here is also robust and has the same breakdown point as the MVE-and MCD-based methods. Furthermore, the computational complexity of the proposed method is significantly smaller than that of other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 12 publications
0
45
0
3
Order By: Relevance
“…A more general presentation and discussion on vector variance can be found in our recent work (Djauhari 2007) [24]. See also (Herwindiati et al, 2007) [26] for its application in robust estimation of location and scatter.…”
Section: Vector Variancementioning
confidence: 99%
See 3 more Smart Citations
“…A more general presentation and discussion on vector variance can be found in our recent work (Djauhari 2007) [24]. See also (Herwindiati et al, 2007) [26] for its application in robust estimation of location and scatter.…”
Section: Vector Variancementioning
confidence: 99%
“…This is a reason why, in the present paper, we propose VVSV-based statistic instead of Box's M statistic and Jennrich's statistic. It is also due to this advantage that in (Herwindiati et al, 2007) [26] we use VV to increase the computational efficiency in data concentration step of FMCD algorithm. More precisely, we use minimum vector variance (MVV) as the stopping rule to substitute the minimum covariance determinant (MCD) which, as mentioned above, has high computational complexity.…”
Section: Vector Variancementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, as noted by Fauconnier and Haesbroeck (2009), Fast MCD algorithm may return different results when used repeatedly in the same or in different statistical packages and could be more critical when n/p are small. To overcome the weaknesses of Fast MCD algorithm, Herwindiati (2006) proposed minimum vector variance (MVV) as an alternative measure of multivariate data concentration. Herwindiati et al (2007) revealed that MVV was successfully used as an objective function in Fast MCD algorithm to substitute the MCD criterion.…”
Section: Introductionmentioning
confidence: 99%